Cocoa Production Stability in Relation to Changing Rainfall and Temperature in East Java, Indonesia - Edi Santosa; Ginanjar Pramudya Sakti; Muhamad Zainul Fattah; Sofyan Zaman; Ade Wahjar (Journal of Tropical Crop Science, 2018)
Climate change as indicated by rising temperature and changing rainfall pattern has been known to affect cacao production in many production countries. However, studies on the effects of rainfall and temperature variability on the cacao production are rarely reported in Indonesia. Hence, the objective of this study is to evaluate the stability of cocoa production in relation to rainfall and temperature variability in order to develop sustainable production under climate change scenario. Research was conducted at a state owned company in Jember District, East Java, Indonesia from February to June 2015. Production and climatic data of 2010-2015 were evaluated using simple regression and correlation analysis. Results revealed that productivity fluctuated among months and among years. However, the fluctuation among months (s2 = 117.076) was lower than among years (s2 = 311.225). Rainfall and temperature showed variability among months and among years; and the fluctuation among months was lower in both rainfall and temperature. Rainfall at one to four months before harvest correlated with production (r=0.400-0.671; P= 0.000 to 0.001) and temperature at two to four months before harvest determined cocoa production (r=0.371-0.412; P=0.001-0.003). High monthly cocoa production coincided with decreasing temperature and rainfall for 4 to 5 months during pod development. The presented study implies that both short and long term strategies should be implemented under climatic variability to sustain cocoa production. It is recommended to apply production technology to stabilize micro climate temperature and to minimize the impact of high rainfall such as shade plant and canopy manipulation.